The porcupine year - Erdrich, Louise (New York : HarperCollins, 2008)
Twelve-year-old Omakayas, an Ojibwe girl, draws strength from the land and spirits as she and her family endure numerous hardships in their search for a new home in northern Minnesota in 1852.
Maps on endpapers.
Sequel to: The birchbark house and The game of silence.
Book Links (A.L.A.).
School Library Journal starred.
Wilson's Children.
6.4
Keywords: Families -- Superior, Lake, Region -- Juvenile fiction; Indians of North America -- Superior, Lake, Region -- Juvenile fiction; Ojibwa Indians -- Juvenile fiction; Voyages and travels -- Juvenile fiction; Family life -- Superior, Lake, Region -- Fiction; Historical fiction; Indians of North America -- Superior, Lake, Region -- Fiction; Ojibwa Indians -- Fiction; Voyages and travels -- Fiction; Family life -- Lake Superior Region -- Fiction; Historical fiction; Native Americans -- Lake Superior Region -- Fiction; Ojibwa Indians -- Fiction; Voyages and travels -- Fiction; Superior, Lake, Region -- History -- 19th century -- Juvenile fiction; Superior, Lake, Region -- History -- 19th century -- Fiction; Lake Superior Region -- History -- Fiction; Historical fiction